Volume 3 Anthropogenic Compounds Part K 2000
DOI: 10.1007/3-540-48915-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Toxaphene. Analysis and Environmental Fate of Congeners

Abstract: Kurznachrichten 469 in der neuen Auflage praktische Hinweise zur Austauschbarkeit nicht nur der Kohlenhydrate, sondern auch der eiwei& und fetthaltigen Nahrstoffe. Damit haben die fur vemchiedene Tatigkeitsmerkmale des Diabetikers aufgestellten Tagesspeiseplane mit unterschiedlichem Kaloriengehalt eine wertvolle Erganzung erfahren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 167 publications
0
38
0
2
Order By: Relevance
“…Baffin Island and (6) S. Hudson Bay: Muir et al (1999), (7) S. Beaufort Sea: Muir (1994Muir ( , 1996de March et al (1998), (8) E. Beaufort Sea: Muir et al (1990), (9) E. Chukchi Sea, (10) E. Bering Sea and (11) Cook Inlet: Becker et al (1995Becker et al ( , 1997; Krahn et al (1999). 19-20 CHB congeners. Although CHB-26 and -50, reported in this study, are normally among the most abundant CHB congeners found in marine mammal samples (Stern et al, 1992;Muir et al, 1999;Vetter and Oehme, 2000), the small number of congeners reported in this study undoubtedly biases the Svalbard results downwards to some extent.…”
Section: Spatial Trends Of Chb Levelsmentioning
confidence: 58%
“…Baffin Island and (6) S. Hudson Bay: Muir et al (1999), (7) S. Beaufort Sea: Muir (1994Muir ( , 1996de March et al (1998), (8) E. Beaufort Sea: Muir et al (1990), (9) E. Chukchi Sea, (10) E. Bering Sea and (11) Cook Inlet: Becker et al (1995Becker et al ( , 1997; Krahn et al (1999). 19-20 CHB congeners. Although CHB-26 and -50, reported in this study, are normally among the most abundant CHB congeners found in marine mammal samples (Stern et al, 1992;Muir et al, 1999;Vetter and Oehme, 2000), the small number of congeners reported in this study undoubtedly biases the Svalbard results downwards to some extent.…”
Section: Spatial Trends Of Chb Levelsmentioning
confidence: 58%
“…Since octa-and nonachloro CTTs are the bulk of toxaphene residues in higher organisms, it appears that S. multivorans was able to primarily transform those CTTs which are bioaccumulated in higher organisms, namely a small number of hepta-to nonachlorobornanes [12]. In this study, we extracted residues of toxaphene and other chloropesticides from Antarctic bird eggs and treated the purified extracts with cell suspensions of S. multivorans.…”
Section: Introductionmentioning
confidence: 99%
“…The toxaphene has been one of the most heavily used pesticides in the word and is listed among the dirty dozen POPs (Saleh, 1991). The technical toxaphene is a complex mixture of several hundred chlorobornane and others chloroterpene congeners (Vetter and Oehme, 2000).…”
Section: Introductionmentioning
confidence: 99%